(untitled) (Medical Forum Monthly, 2020)
Objective: To study the right ventricle perforation in permanent pacemakers implantation. Study Design: Retrospectively study Place and Duration of Study: This study was conducted at the Department of Cardiology, Hayat Abad Medical Complex, Peshawar and PIMS, Islamabad from 2010 to March 2018. Materials and Methods: According to the protocol of our center, we maintain patients’ records of follow up clinic from 2nd post-operation day and then at six months to one year, interval or more frequently if they are having any symptoms. It includes patient’s symptoms, pacemaker site examination, baseline ECG at arrival and patient device parameters observed on device programmer. Patients are advised echocardiography, x-ray chest postero-anterior view and lateral view and examined under fluoroscopy if there is any suspicion of complication. Data so obtained was analyzed for the frequency of lead perforation using SPSS version 22. Results: Total 1670 different implantable devices record was examined during the study period. There were 535 dual chamber pacemakers, 1030 single chambers pacemakers, CRTP, CRTD and AICD were 45, 10 and 49 respectively. We found only one case of RV lead perforation in a dual chamber pacemaker. Conclusion: Lead perforation in permanent pacemakers is a dreaded complication which can be best prevented by not allowing any tension on lead when it is position in the right ventricle.